2017
DOI: 10.1016/j.medengphy.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood pressure variability upon standing up improves reproducibility of cerebral autoregulation indices

Abstract: Dynamic cerebral autoregulation, that is the transient response of cerebral blood flow to changes in arterial blood pressure, is currently assessed using a variety of different time series methods and data collection protocols. In the continuing absence of a gold standard for the study of cerebral autoregulation it is unclear to what extent does the assessment depend on the choice of a computational method and protocol. We use continuous measurements of blood pressure and cerebral blood flow velocity in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 61 publications
(113 reference statements)
1
33
0
Order By: Relevance
“…This is supported by Panerai et al (2001) who demonstrated that, intact CA was present in all manoeuvres that induced sudden changes in BP in healthy subjects [ 34 ]. A study investigating 18 normotensive patients with intact CA in response to a large increase in arterial BPv (three times greater during standing protocol) showed that CBFVv did not increase by a large amount [ 29 ]. Additionally, Lam et al (2018) observed that in nonstroke patients, CA remained intact in response to GHP [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by Panerai et al (2001) who demonstrated that, intact CA was present in all manoeuvres that induced sudden changes in BP in healthy subjects [ 34 ]. A study investigating 18 normotensive patients with intact CA in response to a large increase in arterial BPv (three times greater during standing protocol) showed that CBFVv did not increase by a large amount [ 29 ]. Additionally, Lam et al (2018) observed that in nonstroke patients, CA remained intact in response to GHP [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in the hyperacute, acute and subacute stages of AIS patients, pre-existing BPv is present and therefore insensitive to the effects of changes in head position [26][27][28]. However, a significant difference in MABPv observed over time (visits 2 and 3) could be explained by the temporal relationship seen during stroke recovery, however, in healthy controls, a significant increase in BPv in response to GHP was seen [18,29]. Assuming this is the response in healthy individuals, it would mean that a physiological improvement post-stroke would lead to responses closer to those of a healthy individual.…”
Section: Ais Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these manoeuvres expose transfer function analysis to the risk of too low gain and phase values in the VLF and low-frequency ranges. Indeed, in a very recent work, by Mahdi et al [27], nearly all of the dynamic cerebral autoregulation (dynCA) parameters investigated decreased in parts significantly after stand up. Similarly, Barnes et al [28] demonstrated that the autoregulatory index (ARI) they used, was significantly reduced after squat/stand manoeuvres compared with the baseline recordings at standing.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we demonstrated a significant increase in CV of MAP during tilting of the bed compared to the resting position. Previous literature showed an improvement of reproducibility of the autoregulation coefficients by inducing blood pressure variability due to a sit-to-stand manoeuvre [ 17 , 18 ]. However, those manoeuvres lead to consistent oscillatory changes that enhance reliability, in contrast with bed tilting.…”
Section: Discussionmentioning
confidence: 99%